Protection techniques in electrical energy systems - Ungrad, Helmut (Marcel Dekker, 1995)
Presenting the theoretical principles for, and current state of, electrical power system protection engineering, this work explains the functions of protection and control equipment. It provides application guidelines for every component to be protected in a system, and examines and compares American, British and continental protection philosophies.